Produksi Pangan Fungsional Alternatif Olahan MAngrove di Kabupaten Purworejo - Wibawanti, Jeki Mediantari Wahyu; Fadhiliya, Lukman; Pamungkas, Sapto; Mudawaroch, Roisu Eny (Universitas Muhammadiyah Magelang, 2018)
Currently, the potential development of alternative functional food comes from various types of leaves and mangrove fruit. One of the coastal areas that have a potential mangrove area is Gedangan Village, Purwodadi District, Purworejo Regency, Central Java. The purpose of this program was to the utilization of mangrove into processed functional food as an effort to improve the economy and environmental conservation through creative small industries that utilize the natural potential. Outcomes of this IbM program were CASEOLARIS of mangrove syrup, JERUJU of mangrove tea and FRUTICA mangrove fruit sweets. Mangrove products were potentially to be developed in Purworejo